What makes risk-averse investors tick? A practitioners guide - Anzel Van den Bergh-Lindeque; Sune Ferreira-Schenk; Zandri Dickason Koekemoer; Thomas Habanabakize (Cogent Economics & Finance, 2022)
The real challenge to many practitioners in the financial and investment sector is to accurately profile risk-averse investors to still be inclusive of these investors in the wealth creation process. This study aims to profile risk-averse investors through a structural equation model based on endogenous and exogenous factors. The final sample size consisted of 463 individual investors in the economic hub of South Africa, Gauteng province. These endogenous and exogenous factors may bring about increases or decreases in the risk tolerance levels of investors and accordingly, influence their decisions to initiate, amend or terminate financial behaviours. These factors significantly contributed towards explaining low-risk tolerance behaviour, which assisted with the successful development of a model to profile the risk tolerance behaviour of risk-averse investors. This risk profiling model makes a remarkable and unique contribution to the field of study and the financial industry, since it will assist financial practitioners to profile the risk tolerance behaviour of risk-averse investors more accurately, which will lead to the successful implementation of investment strategies.
Keywords: 330; risk-averse; investors; low-risk tolerance behaviour; endogenous factors; exogenous factors; risk profiling; investment decisions; structural equation modelling; South Africa